Answer:
(x - 12)²/9
Step-by-step explanation:
y = 3sqr(x) + 12
Make x the subject:
y - 12 = 3sqrt(x)
(y - 12)/3 = sqrt(x)
Square both sides
(y - 12)²/9 = x
Interswitch variables
inverse function is:
(x - 12)²/9
If f(x) = (x + 12)^⅓
Then,
y = (x + 12)⅓
y³ = x + 12
y³ - 12 = x
f inverse:
x³ - 12
Tell him to stop buying shoes, you wouldnt have this questions.
that would be 1/2 :P
Answer:
5/2
Step-by-step explanation:
Given the functions
(a) f(x) = x³ + 5x² + x
(b) f(x) = x² + x
(c) f(x) = -x
Function (a)
f(-x) = (-x)³ + 5(-x)² + (-x)
= -x³ + 5x² - x
= -(x³ - 5x² + x)
The function is neither even nor odd.
Function (b)
f(-x) = (-x)² + (-x)
= -(-x² + x)
The function is neither even nor odd.
Function (c)
f(-x) = -(-x)
= x
= -f(x)
Because f(-x) = -f(x) the function is odd.
Answer: f(x) = -x is an odd function.